(untitled) (Journal of Bangladesh Academy of Sciences, 2011)
The fatty acid composition of the ripe seed oil of Nyctanthes arbor-tristis L. (Bengali: Seuli) were determined by GLC. The major constituent of the oil was found to be stearic acid, 39.06%. The relative percentages of other major fatty acids were found to be lauric acid, (4.46); linoleic acid, (7.89); oleic acid, (7.97). The yield of the seed oil was found to be 7.29% on extraction with pet-ether (b. p. 40°C - 60°C). Acid value of seed oil was found to be 55.44 and suggests that this oil is inedible. DOI: http://dx.doi.org/10.3329/jbas.v35i1.7977 Journal of Bangladesh Academy of Sciences, Vol.35, No.1, 121-124, 2011